2015
DOI: 10.1115/1.4029574
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Unsteady Pressure Pulsation in a Centrifugal Pump With Special Slope Volute

Abstract: Rotor–stator interaction, a major source of high amplitude pressure pulsation and flow-induced vibration in the centrifugal pump, is detrimental to stable operation of pumps. In the present study, a slope volute is investigated to explore an effective method to reduce high pressure pulsation level, and its influence on flow structures is analyzed using numerical simulation. The stress is placed on experimental investigation of unsteady pressure pulsation inside the slope volute pump. For that purpose, pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…To guarantee the computational accuracy, the fine grids were necessarily required by the LES model. Thus, grid cells near the solid wall were encrypted, especially on the surface of the blades, where significant pressure gradients and flow separation may easily occur [12] and [13]. Meanwhile, a detailed grid sensitivity analysis with four different mesh numbers has been carried out, as summarized in Table 2.…”
Section: Mesh Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…To guarantee the computational accuracy, the fine grids were necessarily required by the LES model. Thus, grid cells near the solid wall were encrypted, especially on the surface of the blades, where significant pressure gradients and flow separation may easily occur [12] and [13]. Meanwhile, a detailed grid sensitivity analysis with four different mesh numbers has been carried out, as summarized in Table 2.…”
Section: Mesh Generationmentioning
confidence: 99%
“…The unsteady flow structure of a mixed-flow nuclear reactor coolant pump, especially in certain specific regions, is very important to the safety analysis of a nuclear reactor, as it could generate serious flow-induced vibration, threatening the pump integrity [8]. Therefore, a comprehensive analysis and prediction of pressure pulsation caused by intense rotor-stator interaction are essential for the design of the mixed-flow nuclear reactor coolant pump [12] and [13]. At present, in order to improve the efficiency and stable operation of the nuclear reactor coolant pump, the complicated internal unsteady flow structures should be thoroughly illustrated.…”
mentioning
confidence: 99%
“…In terms of pressure pulsation and radial force, Gao et al [15] studied the static performance and pressure fluctuation of a large centrifugal pump and determined the main frequency of mine monitoring points; their findings agreed well with experimental data. Zhang et al [16] investigated a conventional spiral volute pump and demonstrated how slope volute contributes to the significant decline of pressure pulsation. Pei et al [17][18][19] investigated the flow unsteadiness behavior of a centrifugal pump and reported the significant effect of flow rate on time-averaged unsteadiness and distribution of turbulence intensity.…”
Section: Prefacementioning
confidence: 99%
“…And grid cells near surface were encrypted as shown in Figure 2, especially on the surface where the pressure gradients are large and flow separation easily occurs [17]. The value of maximum layers of boundary layer was set to 20; the thickness of the first layer of boundary layer was less than 0.01 mm in order to ensure the value + ≤ 1 near the wall.…”
Section: Parametersmentioning
confidence: 99%